Introduction of the resection severity index as independent risk factor limiting survival after resection of colorectal liver metastases. (December 2017) - Gwiasda, Jill; Schrem, Harald; Kaltenborn, Alexander; Mahlmann, Jan; Mix, Heiko; Lehner, Frank; Kayser, Nicolas; Klempnauer, Jürgen; Kulik, Ulf
Abstract: Background: The purpose of this study is to evaluate the influence of the recently introduced resection severity index (RSI) in patients with liver resection for hepatocellular carcinoma on survival after resection of colorectal liver metastases. The RSI quantifies pre-operatively the liver cellular damage, liver synthetic function and loss of organ parenchyma. Methods: All consecutive patients who underwent liver resection for metastases of colorectal cancer (CLM) between 2000 and 2015 were included in this study. Risk factors limiting survival were analyzed using univariable and multivariable Cox regression analyses. Results: The median survival after liver resection for CLM was 3.0 years. Significant independent risk factors for mortality were the RSI (p = 0.029; hazard ratio (HR): 1.088, 95%-confidence interval (95%-CI): 1.009–1.174), age at resection in years (p = 0.001; HR: 1.017, 95%-CI: 1.007–1.027), pre-operative hemoglobin level (p = 0.041; HR: 0.932, 95%-CI: 0.891–0.997), the cecum as location of primary CRC (p < 0.001; HR: 2.023, 95%-CI: 1.403–2.833), adjuvant chemotherapy (p < 0.001; HR: 1.506, 95%-CI: 1.212–1.878), local relapse of the primary tumor (p = 0.027; HR: 1.591, 95%-CI: 1.057–2.297), the units of intra-operatively transfused packed red blood cells (p < 0.001; HR: 1.068, 95%-CI: 1.033–1.104), the size of the largest metastasis (p = 0.002; HR: 1.005, 95%-CI: 1.002–1.008) and the metastasis' distance to the resection margin (p = 0.014; HR: 0.984, 95%-CI: 0.972–0.997). Conclusion: The RSI is an independent prognostic factor for survival after liver resection for CLM. Besides the extent of liver resection certain primary tumor characteristics have to be taken into account to ensure long-term survival.